Pengaruh Proporsi Komisaris Independen, Jumlah Direktur, Jumlah Komite Audit, Kepemilikan Saham Institusional, Kepemilikan Saham Manajemen Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan - Ieneke Santoso, Herman Ruslim, (Jurnal Ekonomi, 2018)
This study aims to test the impact ofindependent commissioner, board of directors, audit committee, ownership of institutional and management shares and size of firm to the firm performance of the firms listed at Indonesian Stock Exchange Index LQ45 for two consecutive years of the period  February 2014 to January 2016.  This study use the sampling data of 31 firms  The sampling is based on the method of purposive sampling.  Process of analysis data is carried out with analysis partially first and then analysis simultaneous.  The statistic method used is SPPS ( Statistical Product and Service Solution) to obtain descriptive statistics, correlation of variables and analysis of variance. The result of the partial analysis shows that there are two variable has significant influence to the firm performance which is portion of independent commissioner and ownership of institutional shares.  Whereas, the result of the simultaneous analysis has shows  significant impact.